Cellular communications systems in congested environments : resource allocation and end-to-end quality of service solutions with MATLAB /: resource allocation and end-to-end quality of service solutions with MATLAB. ([2017]) - Ghorbanzadeh, Mo; Abdelhadi, Ahmed; Clancy, Charles
No abstract available